Rituximab Monotherapy in the Management of a Rare Case of an HIV Associated Lymphoproliferative Disorder - Jason Hew; Fauzia Rana; Louise Zhou (Case Reports in Oncological Medicine)
Background. Castleman’s disease (CD), also known as angiofollicular node hyperplasia, is a rare heterogenous lymphoproliferative disorder. This disease exists as two distinct entities: a localized or unicentric CD (UCD) which has a more benign clinical course and multicentric CD (MCD) which is a systemic disease and carries a worse prognosis. MCD is often associated with human immunodeficiency virus (HIV) infection and these patients are usually coinfected with human herpes virus-8 (HHV-8). Rituximab is an anti-CD20 monoclonal antibody that has become integral to the management of this disease. It is used alone or in combination with chemotherapy to treat MCD. Case Report. We describe a case of a 58-year-old man with HIV and HHV-8 MCD and evidence of organ failure with a poor performance status that went into complete remission after four cycles of therapy with weekly rituximab. Conclusion. HIV-MCD can be challenging to diagnose and to manage. Early recognition can reduce morbidity and mortality associated with the disease. Rituximab monotherapy can be used as a safe and effective treatment option in patients with a poor performance status.